Belgium : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper analyzes the challenge of population aging for Belgium. It argues that the aging strategy should be broadened to include more explicitly the objective of raising employment rates to foster potential growth. The paper discusses assumptions underlying the official aging projections, and presents an alternative baseline scenario on the basis of unchanged policies. It discusses the feasibility of strategies that rely exclusively on either fiscal or labor market adjustment, and illustrates the benefits of a two-pronged strategy. The paper also examines employment effects of reductions in labor taxes in a wage-bargaining model.